Sport and physical activities in patients with Chronic Achilles tendon rupture reconstruction using flexor hallucis longus transfer. Issue 3 (14th September 2018) - Manzi, Luigi; Maccario, Camilla; Palanca, Ariel; Di Silvestri, Claudia; Usuelli, Federico Giuseppe
Category: Sports Introduction/Purpose: Neglected or chronic Achilles tendon ruptures can be significantly disabling to patients if the muscle-tendon unit is stretched beyond its normal passive limit. Chronic rupture of the Achilles tendon (delayed diagnosis of more than 4 weeks) can result in retraction of the tendon and inadequate healing. Direct repair may not be possible and clinical results may not be satisfactory especially if the distal stump is grossly tendinopathic and when the defect exceeds 5-6 cm. Methods: We evaluated 9 patients (mean age 63) who underwent flexor hallucis longus transfer for treatment of chronic Achilles tendinopathy between May 2014 and January 2017 at a 12 months follow-up. Our results were measured with the SF-12 survey, AOFAS Ankle-Hindfoot Scale and VAS. Activity levels were determined using the Halasi ankle activity scale and the UCLA score obtained preoperatively and 12 months after surgery. Wound complications and tip-toe stance were also assessed. Results: All patients had a significant improvement of AOFAS, VAS and SF-12 scores. The Halasi activity scale and UCLA score were 5.8 and 8.2 respectively 12 months after surgery. Patient reported outcome measures consistently demonstrated improvement in clinical putcomes at 12 months follow-up. The patients went back to full daily function, could single leg heel raise and were gradually returning to sport. No major complications were recorded. Conclusion: Reconstruction of chronic tears of the Achilles tendon with flexor hallucis longus transfer can achieve satisfactory improvements in clinical outcomes at 1 year follow-up.